THE CHOICE OF THE VARIANT OF THE ORGANIZATION OF HEAT SUPPLY OF RESIDENTIAL BUILDINGS IN THE city district of SAMARA - E. Ermolaev; E. Sklyarova; N. Ushanova (Вестник университета)
The paper considers the options for heat supply of residential buildings, as well as selection of appropriate variant of the heat balance of interests of all participants in the creation of the heating system, life cycle cost review of the options for heat supply. Given the cost efficiency of the proposed variant of the heat.